Anisomorphic cell division by African trypanosomes. - Tyler, K; Matthews, K; Gull, K (2001)
In the bloodstream of a mammalian host, African trypanosomes are pleomorphic; the shorter, non-proliferative, stumpy forms arise from longer, proliferative, slender forms with differentiation occurring via a range of morphological intermediates. In order to investigate how the onset of morphological change is co-ordinated with exit from the cell cycle we first characterized slender form cell division. Outgrowth of the new flagellum was found to occur at a linear rate, so by using outgrowth of the new flagellum as a temporal marker of the cell cycle we were able determine the order in which single copy organelles (nucleus, kinetoplast and mitochondrion) were segregated. We also found that flagellar length was an effective marker of the slender to stumpy differentiation and were, therefore, able to study both cell division and differentiation. When these differentiating cells were compared to cells undergoing proliferative cell division, they were found to be anisomorphic--showing discernible differences not only in the length of their new flagella but also in the shape and size of the cells and their nuclei.